KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP LOYALITAS MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING - Febriani, Reni (SINERGI : Jurnal Riset Ilmiah, 2025)
Providing quality services is one of the main objectives of banking services and efforts to maintain the number of customers. This research was conducted to determine the effect of service quality and customer value on customer loyalty through customer satisfaction as an intervening variable. This study uses a quantitative method with an explanatory survey approach. The object of the research is the savings of currency savings customers at the bjb bank KCK Banten. The study sample was taken as many as 87 people with accidental sampling technique. Data analysis in this study using the SEM-PLS method. Hypothesis test results show that service quality has a positive and significant effect on customer loyalty, customer value has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer satisfaction, customer value has a positive and significant effect on customer satisfaction, but customer satisfaction has no effect on customer loyalty. The mediation test results conclude that customer satisfaction is not able to provide mediation on the effect of service quality on customer loyalty.